Upaya Guru Dalam Meningkatkan Motivasi Belajar Siswa TK Melalui Penerapan Ice Breaking pada Pembelajaran Daring - Christin Marni Tuti Alhans; Wiyun Philipus Tangkin (STKIP Andi Matappa Pangkep, 2022)
In online learning, teachers are required to remain professional in designing learning. It is expected that teachers can increase online learning so that students are motivated to learn. However, in fact, when the author conducted a practicum in one of the kindergartens in Kupang city on 7 July - 27 August 2021, it was found that the behavior of students' learning motivation was low. The behavior of the students that appeared were yawning, sitting back lazily, putting their head on the table, and communicating with people at home, so they didn't pay attention to the teacher. Therefore, the purpose of writing this paper is to examine the efforts of teachers in increasing the learning motivation of kindergarten students to learn online, using descriptive qualitative methods. Teachers as motivators can motivate students through the application of ice breaking. The results of this research show that the application of ice breaking can increase students' motivation in learning. It was concluded that the teacher's efforts to motivate students through ice breaking had a positive impact on students' learning motivation. For further researchers, it is recommended to conduct classroom action research, to get more measurable results.